Emboldening equitable climate adaptation: A handbook for field research leaders - Petesch, Patti; Fisher, Eleanor; Hellin, Jon; Echavez, Chona (International Rice Research Institute, 2025)
The ultimate aim of the Handbook is to strengthen understanding of, support to, and accountability for adaptation processes that generate equity in smallholder communities. Toward this end, the Handbook’s locally led approach seeks to nurture an enabling environment for broad-based individual and collective action on climate adaptation. Deep local knowledge and effective agency—of diverse women and men—are vital for forging more equitable community norms and institutional arrangements. The Handbook also emphasizes the importance of greater capacities among external partners to support these localized processes by prioritizing social equity within their own institutions and programs.